Glucagon-like peptide-2 interferes with the neurally-induced relaxant responses in the mouse gastric strips through VIP release. (June 2020) - Traini, Chiara; Idrizaj, Eglantina; Garella, Rachele; Squecco, Roberta; Vannucchi, Maria Giuliana; Baccari, Maria Caterina
Abstract: Glucagon-like peptide-2 (GLP-2) has been reported to indirectly relax gastric smooth muscle. In the present study we investigated, through a combined mechanical and immunohistochemical approach, whether GLP-2 interferes with the electrical field stimulation (EFS)-induced vipergic relaxant responses and the mechanism through which it occurs. For functional experiments, strips from the mouse gastric fundus were mounted in organ baths for isometric recording of the mechanical activity. Vasoactive intestinal peptide (VIP) immunoreactivity in GLP-2 exposed specimens was also evaluated by immunohistochemistry. In carbachol pre-contracted strips, GLP-2 (20 nM) evoked a tetrodotoxin (TTX)-sensitive relaxation, similar in shape to the TTX-insensitive of 100 nM VIP. In the presence of GLP-2, VIP had no longer effects and no more response to GLP-2 was observed following VIP receptor saturation. EFS (4–16 Hz) induced a fast relaxant response followed, at the higher stimulation frequencies (≥ 8 Hz), by a slow one. This latter was abolished either by GLP-2 or VIP receptor saturation as well as by the VIP receptor antagonist, VIP 6–28 (10 μM). A decrease of VIP-immunoreactive nerve structures in the GLP-2 exposed specimens was observed. These results suggest that, in the mouse gastric fundus, GLP-2 influences the EFS-induced slow relaxant response by promoting neuronal VIP release.